Amyloid-Related Imaging Abnormalities With Anti-amyloid Antibodies for the Treatment of Dementia Due to Alzheimer's Disease - Withington, Charles G.; Turner, R. Scott (Frontiers in Neurology, 2022)
Second-generation anti-amyloid monoclonal antibodies are emerging as a viable therapeutic option for individuals with prodromal and mild dementia due to Alzheimer’s disease (AD). Passive immunotherapy with aducanumab (Aduhelm), lecanemab, donanemab, and gantenerumab all lower CNS amyloid (Aβ) burden but come with a significant risk of amyloid-related imaging abnormality (ARIA) - the most common side effect of this class of drugs. While usually asymptomatic and detected only on brain MRI, ARIA may lead to new signs and symptoms including headache, worsening confusion, dizziness, visual disturbances, nausea, and seizures. In addition, one fatality related to ARIA-E (edema) with aducanumab and one fatality due to ARIA-H (hemorrhage) with donanemab are reported to date. ARIA-E may be associated with excessive neuroinflammation and saturation of perivascular clearance pathways, while ARIA-H may be related to vascular amyloid clearance with weakening and rupture of small blood vessels. The risk of ARIA-E is higher at treatment initiation, in ApoE4 carriers, with higher dosage, and with >4 of microhemorrhages on a baseline MRI. The risk of ARIA-H increases with age and cerebrovascular disease. Dose titration mitigates the risk of ARIA, and contraindications include individuals with >4 microhemorrhages and those prescribed anti-platelet or anti-coagulant drugs. A brain MRI is required before aducanumab is initiated, before each scheduled dose escalation, and with any new neurologic sign or symptom. Management of ARIA ranges from continued antibody treatment with monthly MRI monitoring for asymptomatic individuals to temporary or permanent suspension for symptomatic individuals or those with moderate to severe ARIA on MRI. Controlled studies regarding prevention and treatment of ARIA are lacking, but anecdotal evidence suggests that a pulse of intravenous corticosteroids may be of benefit, as well as a course of anticonvulsant for seizures.